2021
DOI: 10.3390/s21124006
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Cybersickness in Virtual Reality Systems through Foveated Depth-of-Field Blur

Abstract: Cybersickness is one of the major roadblocks in the widespread adoption of mixed reality devices. Prolonged exposure to these devices, especially virtual reality devices, can cause users to feel discomfort and nausea, spoiling the immersive experience. Incorporating spatial blur in stereoscopic 3D stimuli has shown to reduce cybersickness. In this paper, we develop a technique to incorporate spatial blur in VR systems inspired by the human physiological system. The technique makes use of concepts from foveated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Integrating the blur manipulation within a VR environment could be promising and open new possibilities; however, some methodological and practical questions need to be considered. To reduce so-called cybersickness, and also enable depth perception similar to that experienced in the real world, it has been suggested that VR systems should ideally incorporate both depth of field (DoF) and foveated rendering techniques that introduce blur into the visual stimuli (Hussain et al, 2021 ). The former approach involves applying blur to visual stimuli that are located at different physical depths than the focal point.…”
Section: Critical Reflectionmentioning
confidence: 99%
“…Integrating the blur manipulation within a VR environment could be promising and open new possibilities; however, some methodological and practical questions need to be considered. To reduce so-called cybersickness, and also enable depth perception similar to that experienced in the real world, it has been suggested that VR systems should ideally incorporate both depth of field (DoF) and foveated rendering techniques that introduce blur into the visual stimuli (Hussain et al, 2021 ). The former approach involves applying blur to visual stimuli that are located at different physical depths than the focal point.…”
Section: Critical Reflectionmentioning
confidence: 99%
“…Halo screen symptoms may include system characteristics (for example, head tracking, rendering, vision, optical), user interaction factors (lack of motion control, visual acceleration or deceleration, VR experience for a longer duration and frequent head movements in VR games), and personal perception factors (gender, age, history of motion sickness, lack of VR experience) [ 58 ]. Therefore, when designing VR scenes and animations, the experience of cybersickness can be reduced according to the influencing factors of cybersickness [ 59 ]: (1) the user actively controls his viewpoint and adjusts it; (2) avoid or limit linear or angular acceleration or deceleration to reduce stimulation of the vestibular organs; (3) display visual indicators or movement tracks to users; and (4) dynamically blur the unimportant areas.…”
Section: Discussionmentioning
confidence: 99%
“…In order to mimic these two blur effects in VR, researchers explored two blurring solutions: non-salient blurring (Nie et al 2019), and depth-of-field blur (DOF blur) (Hussain et al 2021;Chen et al 2021). Nie et al (2019) presented a novel method by blurring the non-salient area dynamically.…”
Section: Blurring Techniquesmentioning
confidence: 99%
“…The authors indicated that the navigation style determines the effectiveness of such a mitigation method (e.g., it cannot help to decrease the discomfort in rotational movement). Hussain et al (2021) combined two kinds of blur effects, where the overall scene was divided into three sections corresponding to the foveal, near, and mid peripheral regions, and added filter accordingly. The final results indicate a significant reduction of cybersickness with Foveated Depth-of-Field blur.…”
Section: Blurring Techniquesmentioning
confidence: 99%